Outcomes of Intercalary Endoprostheses as a Treatment for Metastases in the Femoral and Humeral Diaphysis - Mahdal, Michal; Pazourek, Lukáš; Apostolopoulos, Vasileios; Adámková Krákorová, Dagmar; Staniczková Zambo, Iva; Tomáš, Tomáš (Current oncology, 2022)
BACKGROUND: The purpose of this study was to evaluate the implant survival, functional score and complications of intercalary endoprostheses implanted for metastatic involvement of the femoral and humeral diaphysis. METHODS: The selected group covered patients with bone metastasis who were surgically treated with an intercalary endoprosthesis between 2012 and 2021. The functional outcome was evaluated with the Musculoskeletal Tumor Society (MSTS) scoring system, and complications were evaluated by using the failure classification for prosthetics designed by Henderson. RESULTS: The mean follow-up was 29.8 months. In our group of 25 patients with 27 intercalary endoprostheses (18 femurs, 9 humeri), there were 7 implant-related complications (25.9%), which were more common on the humerus (4 cases, 44.4%) than on the femur (3 cases, 16.7%). Only type II failure-aseptic loosening (5 cases, 18.5%)-and type III failure-structural failure (2 cases, 7.4%)-occurred. There was a significantly higher risk of aseptic loosening of the endoprosthesis in the humerus compared with that in the femur (odds ratio 13.79, 95% confidence interval 1.22-151.05, p = 0.0297). The overall cumulative implant survival was 92% 1 year after surgery and 72% 5 years after surgery. The average MSTS score was 82%. The MSTS score was significantly lower (p = 0.008) in the humerus (75.9%) than in the femur (84.8%). CONCLUSIONS: The resection of bone metastases and replacement with intercalary endoprosthesis has excellent immediate functional results with an acceptable level of complications in prognostically favourable patients.
Keywords: pooperační komplikace; humerus; Prostheses and Implants; lidé; Diaphyses; Femur; diafýzy; protézy a implantáty; Bone Neoplasms; Humerus; Femoral Neoplasms; Humans; Postoperative Complications; femur; nádory kostí; nádory femuru